Quantitative biogeography of picoprasinophytes establishes ecotype distributions and significant contributions to marine phytoplankton. (13th July 2017) - Limardo, Alexander J.; Sudek, Sebastian; Choi, Chang Jae; Poirier, Camille; Rii, Yoshimi M.; Blum, Marguerite; Roth, Robyn; Goodenough, Ursula; Church, Matthew J.; Worden, Alexandra Z.
Summary: Bathycoccus and Ostreococcus are broadly distributed marine picoprasinophyte algae. We enumerated small phytoplankton using flow cytometry and qPCR assays for phylogenetically distinct Bathycoccus clades BI and BII and Ostreococcus clades OI and OII. Among 259 photic‐zone samples from transects and time‐series, Ostreococcus maxima occurred in the North Pacific coastal upwelling for OI (36 713 ± 1485 copies ml −1 ) and the Kuroshio Front for OII (50 189 ± 561 copies ml −1 ) and the two overlapped only in frontal regions. The Bathycoccus overlapped more often with maxima along Line‐P for BI (10 667 ± 1299 copies ml −1 ) and the tropical Atlantic for BII (4125 ± 339 copies ml −1 ). Only BII and OII were detected at warm oligotrophic sites, accounting for 34 ± 13% of 1589 ± 448 eukaryotic phytoplankton cells ml −1 (annual average) at Station ALOHA's deep chlorophyll maximum. Significant distributional and molecular differences lead us to propose that Bathycoccus clade BII represents a separate species which tolerates higher temperature oceanic conditions than Bathycoccus prasinos (BI). Morphological differences were not evident, but quick‐freeze deep‐etch electron microscopy provided insight into Bathycoccus scale formation. Our results highlight the importance of quantitative seasonal abundance data for inferring ecological distributions and demonstrate significant, differential picoprasinophyte contributions in mesotrophic and open‐ocean waters.